The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.21273/jashs.104.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Fall Defoliation Date and Seasonal Carbohydrate Concentration of Pecan Wood Tissue 1

Abstract: Fall defoliation was followed by a depletion of carbohydrate (CHO) reserves and reduction or prevention of yield if defoliation occurred prior to November 1. Refoliation of August-defoliated trees restored the depleted reserves in current season’s wood tissues by December 1 but either completely prevented or greatly reduced yield the next year. September defoliation caused the greatest depletion of reserves and prevented pistillate or staminate flower production the next year. Defoliation on November 1 had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Ethephon at 3-12 m M was used to induce nearly 100% shuck dehiscence 3 to 6 weeks earlier than normally observed, but also induced high levels of leaf abscission. This effect precludes its use alone as a harvest aid for pecan, because defoliation prior to 1 Nov. will greatly reduce the next year's yield (17) due to the loss of carbohydrates and other assimilates (18). The degree of leaf loss necessary to induce a significant loss to the following year's yield or nut quality is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethephon at 3-12 m M was used to induce nearly 100% shuck dehiscence 3 to 6 weeks earlier than normally observed, but also induced high levels of leaf abscission. This effect precludes its use alone as a harvest aid for pecan, because defoliation prior to 1 Nov. will greatly reduce the next year's yield (17) due to the loss of carbohydrates and other assimilates (18). The degree of leaf loss necessary to induce a significant loss to the following year's yield or nut quality is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is supported by observations that shucks of fruit with a dead or abnormal kernel generally do not dehisce (unpublished observation) and dehiscence of normal fruit can be accelerated by exogenously applied ethylene (4). Field attempts to accelerate dehiscence and advance harvesting by using ethylene-releasing chemicals have been unacceptable due to subsequent leaflet abscission (5,13) and its adverse effect on alternate bearing (12,17,18).The threshold for the dehiscence response is 0.7 ppm less for exogenous ethylene near the time of fruit maturity than is the leaflet abscission process (6). Thus, use of ethylene-releasing chemicals by pecan growers must be preceded or accompanied by chemicals that prevent or retard leaflet abscission, while not interfering with shuck dehiscence.…”
mentioning
confidence: 99%
“…The influence of sink demand on photosyn-thetic and senescence physiology of pecan appears to be an important component of the tree's growth strategy, which directly influences next years' nut crop. Studies have shown that autumn defoliation or heavy pest infestations can reduce or prevent fruit-set the following year (8,26,27), presumably due to limited assimilate reserves. Such factors are especially important to trees producing a heavy nut crop, since the time between the conclusion of kernel filling and leaf drop is critical to the accumulation of assimilates necessary for the next seasons' crop.…”
Section: O L J I____________ I____________i____________ I____________imentioning
confidence: 99%
“…Alternate bearing is a phenomenon nearly ubiquitous to polycarpic trees (18) and is a problem of primary importance to the pecan industry. The casual mechanism is unknown, but is closely linked to tree assimilate reserves (26,27). Trees entering dormancy with low reserves tend to produce weak growth and/ or light (" off" ) crops the following year.…”
mentioning
confidence: 99%
“…Irregular bearing severely limits production of pecan nuts. Correlation of production with carbohydrate reserves indicates that low levels of carbohydrates prevent or reduce nut yield the following year (18,19,25,26). This reduction is attributed partially to rapid dry weight accumulation (24) and to energy utilization associated with kernel filling in the latter part of the growing season (18).…”
mentioning
confidence: 99%